Effect of Aripiprazole on 5-HT2Receptor-mediated Wet-Dog Shake Responses and Disruption of Prepulse Inhibition in Rats - Shuntaro Kohnomi; Katsuya Suemaru; Hiromu Kawasaki; Hiroaki Araki (Elsevier, 2008)
Aripiprazole, an atypical antipsychotic drug, is a D2dopamine-receptor partial agonist, but also has affinity to several serotonin receptors (5-HT1A,2A,2C,7). However, little is known about the contribution of serotonin receptors in the action of aripiprazole. The present study investigated the effects of aripiprazole on 5-HT2Areceptor-mediated behaviors and compared them with the effects on dopamine receptor-mediated behavior in rats. Aripiprazole (10, 30 mg/kg, p.o.) inhibited the stereotyped behavior induced by apomorphine (1 mg/kg, s.c.), a dopamine-receptor agonist, and the wet-dog shake responses induced by DOI (2,5-dimethoxy-4-iodoamphetamine, 2 mg/kg, s.c.), a 5-HT2A-receptor agonist. Moreover, aripiprazole improved the disruption of prepulse inhibition induced by both apomorphine and DOI significantly. These data suggest that not only the dopaminergic system, but also the serotonergic system are involved in the antipsychotic effect of aripiprazole. Keywords:: aripiprazole, 5-HT2Areceptor, 2,5-dimethoxy-4-iodoamphetamine (DOI), apomorphine, prepulse inhibition